American Tablet Co.; Hayden & Balcom, Leather Board; G.H. Loomis, Photographic Gallery - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of American Tablet Co.; Hayden & Balcom, Leather Board; G.H. Loomis, Photographic Gallery from the 1870 Boston City Directory